Sustainable Financial Literacy and Preferences for Sustainable Investments among Young Adults - Armin Varmaz; Katharina Riebe; Sabrina Hegner (Vierteljahrshefte zur Wirtschaftsforschung, 2021)
We use a choice experiment on equity fund investments to estimate the preferences of young adults for sustainable investments relative to conventional investment funds. Our results suggest that the traditional trade-off between investment fund risk and return is still valid in the selection of sustainable investment funds. The environment focus is more important for the choice of sustainable investment then social or governance aspects. Latent behavioural characteristics (conscientiousness, importance of the impact of direct investments on sustainability, risk aversion, financial literacy) are also important to explain the choice for sustainable funds. – – In diesem Beitrag verwenden wir ein Auswahlexperiment bzgl. der Auswahl von Aktienfonds, um die Präferenzen junger Erwachsener für nachhaltige Anlagen im Vergleich zu konventionellen Investmentfonds zu schätzen. Unsere Ergebnisse deuten darauf hin, dass der traditionelle Trade-Off zwischen dem Risiko und der Rendite von Aktienfonds auch bei der Auswahl nachhaltiger Investmentfonds Bestand hat. Der Fokus auf die Umwelt ist bei der Wahl nachhaltiger Anlagen wichtiger als soziale oder Governance-Aspekte. Latente Verhaltensmerkmale (Gewissenhaftigkeit, Bedeutung der Auswirkungen von Direktinvestitionen auf die Nachhaltigkeit, Risikoaversion, Finanzwissen) sind ebenfalls wichtig, um die Entscheidung für nachhaltige Fonds zu erklären.
Keywords: G53; G11; G41; C52; C91; A13; 330; portfolio choice; sustainable investments; Socially responsible investments; Ethical investing; Corporate social responsibility; equity funds; financial literacy